CASE STUDY: IMPLEMENTASI FISIOTERAPI PADA KONDISI DOWN SYNDROME DENGAN MODALITAS NEURO DEVELOPMENTAL TREATMENT (NDT), SENSORY INTEGRASI (SI) DAN PLAY EXCERCISE (PE) - Anisa Dwi Kusuma Ningrum; Nur Susanti (SINERGI : Jurnal Riset Ilmiah, 2026)
Down Syndrome is a condition of delayed physical and mental development caused by chromosomal abnormalities. These chromosomal changes cause various disorders, such as hypotonia, motor control weakness, and coordination disorders that impact children's gross motor skills, fine motor skills, language, cognitive, social, and emotional development. This study aims to determine the effectiveness of physiotherapy management using Neuro Developmental Treatment (NDT), Sensory Integration (SI), and Play Exercise (PE) modalities in children with Down Syndrome. The study used a descriptive analytical method with a Case Study design on a 10-year-old girl who underwent three therapy sessions at YPAC Prof. Dr. Soeharso Surakarta. Data were collected through hetero anamnesis with instruments for examining tone, muscle strength, balance, posture, sensory, and functional activities. The results showed an increase in muscle tone, core muscle strength, balance on PBS points Standing with Feet Together and Standing with Feet in Front, an increase in posture scores to 85 out of 100, and an increase in functional activity abilities in dimension E (walking, running, and jumping). Sensory impairments were still found in the visual, auditory, proprioceptive, and vestibular aspects. It was concluded that NDT, SI, and PE modalities were effective in improving muscle tone, strength, balance, sensory responses, and functional activity abilities in children with Down syndrome, although postural improvement did not show significant improvement.